Cativic acid-caffeic acid hybrid exerts cytotoxic effects and induces apoptotic death in human neuroblastoma cells - Alza, Natalia Paola (2017)
Background: The development of hybrids from natural products is a promising strategy for drug discovery. In cancer therapy, there is a need to discover novel agents that can induce apoptosis in cancer cells. To contribute to this field of interest, we investigated the effect of a synthetic hybrid from cativic acid and caffeic acid (5) on viability, proliferation and apoptosis in human neuroblastoma cells (IMR-32). Methods: Three hybrids were prepared via Mitsunobu esterification from 17-hydroxycativic acid (1) and natural phenols. Cell viability was analyzed by MTT assay. SYTOX green and LDH leakage were used to determine the cytotoxic effect. Caspase-3 activity, cell cycle phases and proliferation were analyzed in order to characterize the biological effects of hybrid 5. The mitogen-activated-protein kinase (MAPK) status was evaluated for elucidating the potential mechanisms involved in hybrid 5 effect. Results: Hybrid 5 reduced the viability of IMR-32 cells in a time- and concentration-dependent manner (IC50 = 18.0 ± 1.3 μM) as a result of its antiproliferative effect through changes in the cell cycle distribution and induction of apoptosis associated with activation of caspase-3. Exposure to 5 triggered ERK1/2 activation and nuclear translocation. Hybrid 5 also promoted an increase in nuclear localization of the transcription factor c-Jun. Inhibition of ERK1/2 and JNK potentiated 5-induced inhibition of IMR-32 viability.Conclusion: Hybrid 5 displays cell growth inhibition by promoting cell cycle arrest and apoptosis, through ERK1/2 and JNK participation.